Motorola solutions CEO shared experience on six sigma in the CEO@faculty programme - Nor Fadzillah, Zulkipli (Pejabat Naib Canselor, 2016)
It was an enlightening experience for Universiti Malaysia Pahang (UMP) lecturers and students who turned up to listen to a talk by Managing Director of Motorola Solutions Malaysia, Penang Operations Dr. Hari Narayanan on March 9, 2016.